2019
DOI: 10.5937/zembilj1901001p
|View full text |Cite
|
Sign up to set email alerts
|

Eluvial losses of Ca from Umbric Albeluvisols Abruptic produced by different doses of lime: Column experiment

Abstract: Losses of soil calcium due to migration from Umbric Albeluvisols Abruptic soil meliorated by various doses of chalk were studied in column experiment with 16 washings. It has been established that the dynamic of calcium leaching from soil limed with optimal dose (1) and increased dose (2) is of a similar nature. In both treatments in the first 5 and 3 washes, respectively, there was a sharp decrease in the amount of calcium in the soil as described by exponential model. Starting from 6 and 4 washes, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Ghimire et al (2017) found that surface soil pH dropped from 5.70 in control conditions to 5.0 after 70 years of N-application . This study confirmed that the continuous addition of mineral N results in a constant gradual decrease in pH, accompanied by the loss of basic cations (Ca 2+ , K + , Mg 2+ ) due to leaching (Pavlova et al, 2019). This, in turn, leads to a decrease in base saturation and an increase in Al 3+ saturation, and thus the availability of nutrients is reduced (Goulding, 2016).…”
Section: Soil Phsupporting
confidence: 79%
“…Ghimire et al (2017) found that surface soil pH dropped from 5.70 in control conditions to 5.0 after 70 years of N-application . This study confirmed that the continuous addition of mineral N results in a constant gradual decrease in pH, accompanied by the loss of basic cations (Ca 2+ , K + , Mg 2+ ) due to leaching (Pavlova et al, 2019). This, in turn, leads to a decrease in base saturation and an increase in Al 3+ saturation, and thus the availability of nutrients is reduced (Goulding, 2016).…”
Section: Soil Phsupporting
confidence: 79%
“…The Department of Soil Science and Agrochemistry of the St. Petersburg State Agrarian University (Russia), together with the Agrophysical Research Institute (St. Petersburg, Russia) has been dealing with the problem of using non-traditional chemical ameliorants (local lime materials and industrial waste) for liming acidic soils (Litvinovich et al, 2001(Litvinovich et al, , 2013(Litvinovich et al, , 2016(Litvinovich et al, , 2017(Litvinovich et al, , 2018(Litvinovich et al, , 2019a(Litvinovich et al, , 2019b(Litvinovich et al, , 2020Pavlova et al, 2019aPavlova et al, , 2019cPavlova et al, , 2020Lavrishchev et al, 2017). The widespread use of these materials is limited by the presence of harmful impurities in their composition that can have a negative effect on soils and plants.…”
Section: Introductionmentioning
confidence: 99%